2021
DOI: 10.3390/vaccines9050504
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Leftover Serosurvey of SARS-CoV-2 IgG Antibodies in Greece, May to August 2020

Abstract: A serosurvey of IgG antibodies against SARS-CoV-2 was conducted in Greece between May and August 2020. It was designed as a cross-sectional survey and was repeated at monthly intervals. The leftover sampling methodology was used and a geographically stratified sampling plan was applied. Of 20,110 serum samples collected, 89 (0.44%) were found to be positive for anti-SARS-CoV-2 antibodies, with higher seroprevalence (0.35%) observed in May 2020. The highest seroprevalence was primarily observed in the “30–49” y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(22 reference statements)
3
4
1
Order By: Relevance
“…Our IFR estimate among older individuals was only slightly lower than the 6.9% recently reported from rural settings in Latin America [17]. These estimates for the elderly population are, as expected, much higher than previously reported estimates for all ages from Greece [18], China [19], and cruise ships [20] as well as the estimate we reported in the younger donor population [4].…”
Section: Resultscontrasting
confidence: 69%
“…Our IFR estimate among older individuals was only slightly lower than the 6.9% recently reported from rural settings in Latin America [17]. These estimates for the elderly population are, as expected, much higher than previously reported estimates for all ages from Greece [18], China [19], and cruise ships [20] as well as the estimate we reported in the younger donor population [4].…”
Section: Resultscontrasting
confidence: 69%
“…In total, 89 (3.94%) of the participants reported that they had, or currently have been diagnosed with COVID-19; of these, 36 were men (3.95%, mean age 33 (SD 13) years) and 53 were women (3.94%, age 32 (SD 16) years) (p-value for sex comparisons ¼ 0.82). The incidence of COVID-19 observed in this survey is in line (adjusted for period effect) with reports from seroepidemiological studies conducted in Greece during the past months (Bogogiannidou et al, 2020;Tsitsilonis et al, 2020).…”
Section: Resultssupporting
confidence: 90%
“…From March 2020 to present, an ongoing national initiative has been implemented in Greece, systematically monitoring the seroprevalence in leftover serum samples at monthly intervals, covering the vast majority of regional units in the country. Previously published reports indicate low percentages of seropositivity in Greece until August 2020 [ 6 , 7 ], which is in accordance with low levels of virus circulation until that period. Seroprevalence at a national scale had been consistently estimated to be lower than 0.5% for the period between March to August 2020, while the cumulative incidence of COVID-19 based on reported cases was approximately 0.1% by 30 August 2020.…”
Section: Introductionsupporting
confidence: 75%
“…The statistical analysis applied is based on the methodology that was applied for samples between March and August 2020 [ 6 , 7 ], with some modifications. Analysis was performed with the use of IMB SPSS Statistics V22.0 and Microsoft Excel.…”
Section: Methodsmentioning
confidence: 99%